Prophets beyond activism: rethinking the prophetic roots of social justice - O'Brien, Julia M. (Westminster John Knox Press, 2024)
Prophets beyond Activism insightfully challenges the common progressive narrative that the prophets of ancient Israel were primarily concerned with social justice. Instead it daringly offers more life-giving ways of engaging the prophetic books for the causes of justice.